Preparation method and application of nanofiber composite aerogel freshness indicating label
PVDF nanofiber aerogels were prepared by electrospinning and freeze-drying techniques, which solved the problem of slow response in existing meat freshness detection methods and enabled rapid and sensitive detection of meat spoilage, making it suitable for food safety monitoring.
Patent Information
- Application Number
- CN202511360551.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-23
- Publication Date
- 2025-12-09
AI Technical Summary
Existing methods for detecting meat freshness suffer from slow response times and insignificant color changes, making it difficult to monitor pH fluctuations or gas concentration changes in the early stages of meat spoilage in real time.
PVDF nanofiber frameworks were prepared using electrospinning technology, anthocyanin-based intelligent response units were integrated, and a three-dimensional nanofiber aerogel structure with interconnected porous channels was formed through freeze-drying.
It enables rapid and sensitive detection of meat freshness, and indicates the degree of spoilage in real time through the color change of aerogel, simplifying the detection process and making it suitable for food safety monitoring.
Smart Images

Figure CN121086327A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of food packaging storage and detection, and particularly relates to a preparation method of a nanofiber composite aerogel freshness indicating label and application thereof. BACKGROUND
[0002] Meat products, as an important source of high-quality animal protein, are deeply welcomed by consumers. However, during daily storage and transportation, factors such as microbial contamination, lipid oxidation, protein degradation, and myoglobin discoloration can easily lead to meat spoilage. Along with the spoilage process, the pH of the meat increases significantly, and a series of characteristic metabolic gases are produced, including carbon dioxide (CO2), hydrogen sulfide (H2S), and nitrogen-containing compounds (such as total volatile basic nitrogen, TVB-N). These unfavorable physical and chemical changes not only seriously affect the sensory quality and nutritional value of meat, but also significantly shorten its shelf life, posing a potential food safety risk. Therefore, it is crucial to assess the freshness and safety of meat in a timely and effective manner.
[0003] Traditional meat freshness detection methods (such as chemical analysis) are relatively accurate, but they usually require professional laboratory environments, involve complex sample pretreatment and analysis processes, are time-consuming and labor-intensive, and cannot meet the needs of real-time, in-situ monitoring. Given the significant time sensitivity of meat spoilage processes, developing intelligent indicating technologies that can reflect changes in meat freshness in real time has become a research hotspot in recent years.
[0004] Intelligent indicating labels, especially those based on colorimetric principles, are considered a promising solution due to their non-invasive, easy-to-use, and intuitive visual advantages. An ideal indicating label should be able to sensitively detect and quickly respond to small changes in key indicators related to meat spoilage, such as specific gas or pH changes. However, existing indicating labels, especially traditional labels with dense structures, often have slow response speeds and insignificant color changes, making it difficult to effectively capture the rapid pH fluctuations or gas concentration changes that occur at the early stages of meat spoilage. Although electrospinning technology has been used to prepare two-dimensional (2D) nanofiber indicating labels with higher specific surface areas, the relatively flat pore structure still limits the rapid diffusion and adsorption of target gas molecules to some extent, and the response sensitivity and speed need to be further improved.
[0005] In this context, aerogel materials with three-dimensional (3D) porous network structures have attracted extensive attention due to their ultra-high porosity (typically > 90%), extremely large specific surface area, extremely low density, and tunable pore structure. Aerogels are usually prepared by a sol-gel process combined with supercritical drying or freeze-drying techniques, and their unique structural characteristics enable them to exhibit significant advantages in gas adsorption, mass transfer and diffusion, and sensing response. Assembling nanofibers (such as those prepared by electrospinning) into aerogel structures not only inherits the high specific surface area characteristics of nanofibers, but also constructs through three-dimensional multi-level channels, greatly promoting the rapid adsorption, diffusion of spoilage gases, and sufficient contact with indicators, thereby enabling faster and more sensitive colorimetric responses.
[0006] Therefore, in order to overcome the defects of existing indicator labels such as response lag and insufficient sensitivity, there is an urgent need to develop a method for preparing a three-dimensional nanofiber aerogel indicator label with high sensitivity and fast response characteristics. SUMMARY
[0007] The present application provides a preparation method and application of a 3D porous nanofiber composite aerogel based on polyvinylidene fluoride (PVDF). A PVDF nanofiber skeleton is constructed by electrospinning, an intelligent response unit is integrated with anthocyanin, and a aerogel with through-porous structure is formed by freeze-drying process. The indicating effect of the aerogel on meat is verified by measuring indicators such as TVB-N; the synthesized aerogel has the comprehensive characteristics of environmental friendliness, high porosity, fiber network and excellent freshness indicating performance.
[0008] To achieve the above purpose, the present application adopts the following technical scheme; a preparation method of a nanofiber composite aerogel freshness indicator label, specifically comprising the following steps:
[0009] Step one: extraction of anthocyanin:
[0010] The raw material containing anthocyanin is washed and dried, the dried raw material is crushed, and the powder is collected after screening through a screen. The powder is added to ethanol to form a mixed solution; the obtained mixed solution is stirred and extracted in the dark, filtered after stirring and extraction, and then evaporated and dried to remove ethanol. The remaining residual solution is the anthocyanin extract;
[0011] Step two: preparation of spinning solution:
[0012] PVDF and polyvinylpyrrolidone are dissolved in a N-N dimethylformamide and acetone double solvent system, stirred and dissolved at room temperature, and a spinning solution is obtained after standing and defoaming;
[0013] Step three: preparation of nanofibers using electrospinning technology:
[0014] The spinning solution prepared in step two is spun by electrospinning technology. First, the spinning solution prepared in step two is injected into a syringe. Then, the spinning parameters are set, and tin foil paper is used as the receiving substrate and collected by a rotating drum. Finally, polyvinylidene fluoride composite nanofibers are obtained.
[0015] Step four: prepare nanofiber aerogel by freeze-drying technology:
[0016] The polyvinylidene fluoride composite nanofibers obtained in step three and the anthocyanin extract obtained in step one are added to a mixed solution of tert-butyl alcohol and ultrapure water, and then water-based polyurethane is added as an adhesive. After homogenization, a polyvinylidene fluoride short fiber dispersion solution is obtained. Then, the polyvinylidene fluoride short fiber dispersion solution is pre-frozen and then freeze-dried to obtain a nanofiber composite aerogel freshness indicator label.
[0017] Preferably, the raw material containing anthocyanins in step one includes black medlar, purple cabbage, and butterfly pea anthocyanins. The drying temperature is 30-50℃, and the time is 24-48h. The mesh size of the screen is 40-50 mesh. The powder and ethanol are used in a ratio of 1kg:10L.
[0018] Preferably, the stirring extraction time in step one is 8-12h, and the evaporation drying temperature is 45-50℃, and the evaporation time is 2-2.5h.
[0019] Preferably, in the spinning solution in step two, the mass fraction of PVDF is 10-16%; the mass fraction of polyvinylpyrrolidone in the spinning solution is 5%; the volume ratio of N-N dimethylformamide and acetone solution is 4-2:1; the stirring time at room temperature is 2-4h; and the defoaming time is 10-12h.
[0020] Preferably, in step three, the spinning parameters are set as follows: the voltage applied by the high-voltage power supply is 6KV, the receiving distance is 15-20cm, the solution advancing rate is 1mL / h, the spinning temperature is 30-35℃, and the relative humidity is 40%-50%.
[0021] Preferably, in step four, the volume ratio of tert-butyl alcohol and ultrapure water is 4:1, the amount of polyvinylidene fluoride composite nanofibers is 0.5-3wt% of the mass of the polyvinylidene fluoride short fiber dispersion solution, the amount of anthocyanin extract is 3-7wt% of the mass of the polyvinylidene fluoride short fiber dispersion solution, and the amount of water-based polyurethane is 3-5wt% of the mass of the polyvinylidene fluoride short fiber dispersion solution. The homogenization conditions are: rotation speed 8000rpm, time 3min.
[0022] Preferably, the pre-freezing condition in step four is -20 DEG C, 20-24h; the freeze-drying condition is -50 DEG C, 10Pa, and the time is 24-36h.
[0023] The use of the nanofiber indicating aerogel freshness indicating label for detecting the freshness of meat, the specific steps are as follows:
[0024] The nanofiber aerogel is cut into a suitable size, placed in the meat packaging container, and kept physically isolated from the meat (2-10cm apart); as the storage time is prolonged, the meat continuously releases the characteristic volatile gas of spoilage, the gas enters the porous structure of the indicating label through diffusion, and a combination reaction occurs with the cyanine substance loaded on the aerogel, triggering the color change of the label; when the meat changes from fresh to not fresh, the color of the corresponding indicating film changes, thereby indicating the freshness state of the meat; thus, the freshness of the meat can be judged in time according to the color change, realizing visual detection.
[0025] By using the above scheme, the application has the following beneficial effects:
[0026] (1) The nanofiber aerogel indicating label prepared by three-dimensional reconstruction in the application has a unique multi-level pore structure, wherein the primary pores formed by the stacking of nanofibers and the secondary pores produced by the sublimation of ice crystals during freeze-drying cooperate to form a highly interconnected three-dimensional porous network. The structure provides an efficient mass transfer channel for the spoilage gas molecules, significantly enhancing their contact efficiency with the cyanine indicator, thereby greatly shortening the response time and improving the detection sensitivity.
[0027] (2) The nanofiber aerogel prepared in the application is optimized in terms of structural performance, the polyvinylidene fluoride nanofiber skeleton provides stable three-dimensional support, and the waterborne polyurethane adhesive strengthens the bonding of fiber nodes through intermolecular forces. The traditional nanocellulose preparation process is omitted, and the two-dimensional nanofiber structure is directly converted into a three-dimensional structure. In particular, when the amount of waterborne polyurethane is limited to a specific ratio range, the effective bonding between fibers can be ensured (to avoid structural defects), and the pore patency can be maintained (to prevent adhesive blockage).
[0028] (3) The blending electrospinning of polyvinylidene fluoride and polyvinylpyrrolidone used in the application produces a synergistic effect: polyvinylpyrrolidone not only improves the uniformity of the fiber morphology during spinning, but also selectively dissolves out to form a surface microporous structure during subsequent processing, significantly increasing the specific surface area of the aerogel and providing abundant loading sites for cyanine.
[0029] (4) The application is prepared by electrospinning combined with freeze-drying technology, which is simple and suitable for large-scale production. The obtained indicating label is in the form of nanofiber aerogel, which has the characteristics of light weight (the density is only 0.032g / cm3 ), which can be directly applied to products to avoid additional weight gain.
[0030] (5) The prepared nanofiber aerogel can fully utilize the advantages of 3D porous structure, and can indicate the spoilage degree of perishable food such as meat in real time and intuitively, thereby providing an effective technical means for guaranteeing food safety and reducing food loss. BRIEF DESCRIPTION OF DRAWINGS
[0031] Figure 1 is a flowchart of the nanofiber composite aerogel freshness indicating label prepared by the present application.
[0032] Figure 2 is a scanning electron microscope image of the nanofiber composite aerogel freshness indicating label prepared in Example 1 of the present application, wherein A is an image of the nanofiber composite aerogel freshness indicating label under 100 microns, B is an image of the nanofiber composite aerogel freshness indicating label under 10 microns, and C is an image of the nanofiber composite aerogel freshness indicating label when the waterborne polyurethane addition amount exceeds 5wt%.
[0033] Figure 3 is a density and porosity graph of the nanofiber composite aerogel freshness indicating label prepared in Example 2 of the present application.
[0034] Figure 4 is a TVB-N change graph (A) in the actual application process of chilled meat and a real-time indication graph (B) of the nanofiber composite aerogel freshness indicating label in Example 3 of the present application. DETAILED DESCRIPTION
[0035] In order to make the purpose, technical scheme and advantages of the present application clearer, the present application will be further described in detail below in combination with the drawings and examples. It should be understood that the specific examples described herein are only used to explain the present application and do not limit the present application. The flowchart of the nanofiber composite aerogel freshness indicating label prepared by the present application and the detection application flowchart are shown in Figure 1 , and the specific operation is shown in the examples.
[0036] Example 1:
[0037] (1) Extraction of anthocyanins:
[0038] Select purple cabbage as raw material, remove damaged tissue, stem, etc., wash with distilled water, dry in an oven at 30°C for 24h, obtain dried material, then crush the purple cabbage with a pulverizer and pass through a 40 mesh sieve to obtain powder. Add 70g of the powder to 700mL of 75% ethanol and stir at room temperature for 12h. Then, remove insoluble substances and other non-hydrophilic materials by vacuum filtration through filter paper, and collect the extract. The resulting extract is evaporated and dried at 45°C for 2.5h using a rotary evaporator to remove ethanol, obtaining a concentrated extract (i.e., the anthocyanin extract). The concentrated extract is stored at low temperature and protected from light.
[0039] (2) Preparation of the spinning solution:
[0040] The mixed solvent is prepared by mixing N,N-dimethylformamide and acetone at a volume ratio of 4:1. PVDF and polyvinylpyrrolidone are added to the mixed solvent to form a mixed solvent system. In the mixed solvent system, the mass fraction of PVDF solid particles is 12%, and the mass fraction of polyvinylpyrrolidone is 5%.
[0041] The mixed solvent system is continuously stirred at a speed of 800 rpm at room temperature for 4h. After standing for 12h to remove bubbles, a bubble-free and phase-separated spinning solution is obtained for electrospinning.
[0042] (3) Preparation of composite nanofibers using electrospinning technology:
[0043] An electrospinning machine is used to spin the spinning solution. A drum receiving device is used to prepare composite nanofibers with uniform thickness. The spinneret fixed on the receiving device can move linearly at a constant speed. First, transfer the spinning solution to the push pump, adjust the push pump to fill the plastic tube with the spinning solution, and finally connect the high-voltage power supply. The positive electrode of the power supply is connected to the needle, and the receiving device and the push pump are connected to the ground. Cover the drum receiving device with a layer of tin box paper to support the nanofibers. Adjust the working parameters, the receiving distance is 15cm, the power supply voltage is 6KV, and the push pump flow rate is 1mL / h. Use an air conditioner and a dehumidifier to control the environmental temperature to 30°C and the relative humidity to 40%. After 72h, the nanofibers are prepared, the tin paper is placed in an oven at 35°C for drying, and finally the polyvinylidene fluoride composite nanofibers are obtained.
[0044] (4) Preparation of composite nanofiber aerogel using freeze-drying technology:
[0045] A mixed solvent was prepared by mixing tert-butyl alcohol and ultrapure water at a volume ratio of 4:1 (v / v), adding the anthocyanin extract obtained in step (1) and the polyvinylidene fluoride nanofiber obtained in step (3), and then adding aqueous polyurethane (solid content 35%), and then homogenizing at 8000 rpm for 3 min to form a stable dispersion, which is the polyvinylidene fluoride short fiber dispersion; wherein the amount of anthocyanin extract is 4wt% of the mass of the polyvinylidene fluoride short fiber dispersion, the amount of polyvinylidene fluoride composite nanofiber is 2wt% of the mass of the polyvinylidene fluoride short fiber dispersion, and the amount of aqueous polyurethane is 4wt% of the mass of the polyvinylidene fluoride short fiber dispersion;
[0046] Transfer to 48-well mold and directional freeze at -20℃ for 24h to construct ice crystal template, finally freeze-dried at -50℃, 10Pa for 24h to obtain nanofiber composite aerogel freshness indicator label with hierarchical porous structure.
[0047] To verify the internal structure of the nanofiber composite aerogel, scanning electron microscopy was used to observe at 100 microns and 10 microns, respectively. As shown in Figure 2 , where Figure A is the image of the nanofiber composite aerogel at 100 microns, and Figure B is the image of the nanofiber composite aerogel at 10 microns, it can be seen that the aerogel has interconnected macroporous structure, which is beneficial to the exchange of spoilage gases. These macropores are composed of nanofiber filaments, which further increase the specific surface area of the material, thereby promoting the adsorption rate of anthocyanin to spoilage gases. When the amount of aqueous polyurethane exceeds 5wt% (the specific amount is 6%), as shown in Figure 2 C, excessive adhesion causes the fibers to aggregate together, which is not conducive to maintaining the porous structure and gas diffusion channels of the aerogel, thus leading to a decrease in the specific surface area of the aerogel and a decrease in response sensitivity. Too little amount of aqueous polyurethane (<3wt%) will result in a loose structure and easy breakage, and cannot form a complete aerogel.
[0048] Example 2:
[0049] (1) Extraction of anthocyanin:
[0050] The selected butterfly pea petals were removed from damaged tissues, stems, etc., washed with distilled water, and placed in an oven at 40℃ for 36h to dry. The dried material was then crushed with a grinder and passed through a 45-mesh sieve to obtain a powder. 70g of the powder was added to 700mL of 75% ethanol and stirred at room temperature for 12h. Then, the insoluble substances and other non-hydrophilic materials were removed by vacuum filtration with filter paper. The resulting extract was evaporated and dried at 47℃ for 2.5h using a rotary evaporator to remove ethanol, obtaining a concentrated extract (i.e. anthocyanin extract). The concentrated extract was stored at low temperature and protected from light.
[0051] (2) Preparation of the spinning solution:
[0052] The mixed solvent was prepared by mixing N,N-dimethylformamide and acetone at a volume ratio of 2:1. PVDF and polyvinylpyrrolidone were added to the mixed solvent to form a mixed solvent system. In the mixed solvent system, the mass fraction of PVDF solid particles was 16%, and the mass fraction of polyvinylpyrrolidone was 5%.
[0053] The mixed solvent system was continuously stirred at a speed of 8000 rpm for 3 hours at room temperature. After standing for 12 hours to remove bubbles, a bubble-free and phase-separated spinning solution was obtained for electrospinning.
[0054] (3) Preparation of composite nanofibers using electrospinning technology:
[0055] The spinning solution was spun using an electrospinning machine. A drum receiving device was used to prepare composite nanofibers with uniform thickness. The spinneret fixed on the receiving device could move linearly at a constant speed. First, the spinning solution was transferred to the push pump, and the push pump was adjusted until the spinning solution filled the plastic tube. Finally, the high-voltage power supply was connected, with the positive electrode connected to the needle and the receiving device and push pump connected to the ground. A layer of tin box paper was placed on the drum receiving device to support the nanofibers. The working parameters were adjusted, with a receiving distance of 18 cm, a power supply voltage of 6 KV, and a push pump flow rate of 1 mL / h. The environmental temperature was controlled at 33°C and the relative humidity was 45% using an air conditioner and dehumidifier. After 72 hours, the nanofibers were prepared, the tin paper was placed in an oven at 35°C for drying, and finally the polyvinylidene fluoride composite nanofibers were obtained.
[0056] (4) Preparation of composite nanofiber aerogel using freeze-drying technology:
[0057] A mixed solvent was prepared by mixing tert-butyl alcohol and ultrapure water at a volume ratio of 4:1 (v / v). The cyanidin extract obtained in step (1) and the polyvinylidene fluoride nanofibers obtained in step (3) were added, followed by the addition of water-based polyurethane (solid content 35%). The mixture was homogenized at 8000 rpm for 3 minutes to form a stable dispersion, which was the polyvinylidene fluoride short fiber dispersion. The amount of cyanidin extract was 5wt% of the mass of the polyvinylidene fluoride short fiber dispersion, the amount of polyvinylidene fluoride composite nanofiber was 3wt% of the mass of the polyvinylidene fluoride short fiber dispersion, and the amount of water-based polyurethane was 4wt% of the mass of the polyvinylidene fluoride short fiber dispersion.
[0058] The mixture was transferred to a 48-well mold and directionally frozen at -20°C for 24 hours to construct an ice crystal template. Finally, the mixture was freeze-dried at -50°C and 10 Pa for 24 hours to obtain a nanofiber composite aerogel freshness indicator label with hierarchical pore structure.
[0059] To verify the lightweight porous characteristics of the nanofiber composite aerogel, the porosity and density of the nanofiber composite aerogel were determined (density determination refers to GB / T 6343-2009, and porosity determination uses the mercury injection method). As shown in FIG. 8, the aerogel has a porosity of 98.36% and a density of 0.032 g / cm3. Figure 3 As shown in FIG. 8, the aerogel has a porosity of 98.36% and a density of 0.032 g / cm3. 3 This indicates that the material has low density and high porosity, which is determined by the nature of PVDF and electrospinning and freeze-drying methods. The relatively lightweight PVDF nanofiber has a small weight after stacking, and the high-porosity structure provides an ideal channel and surface for the diffusion of spoilage gases and the adsorption of anthocyanins.
[0060] Example 3:
[0061] (1) Extraction of anthocyanins:
[0062] The selected black wolfberry fruits were removed from damaged tissues, stems, etc., washed with distilled water, and dried in an oven at 45°C for 48h. The dried material was then crushed with a pulverizer and passed through a 50-mesh sieve to obtain a powder. 70g of the powder was added to 700mL of 75% ethanol and stirred at room temperature for 12h. Then, the insoluble substances and other non-hydrophilic materials were removed by vacuum filtration with filter paper. The resulting extract was evaporated and dried at 50°C for 2.5h using a rotary evaporator to remove ethanol, obtaining a concentrated extract (i.e., the anthocyanin extract). The concentrated extract was stored at low temperature and protected from light.
[0063] (2) Preparation of the spinning solution:
[0064] The mixed solvent was prepared by mixing N,N-dimethylformamide and acetone at a volume ratio of 3:1. PVDF and polyvinylpyrrolidone were added to the mixed solvent to form a mixed solvent system. In the mixed solvent system, the mass fraction of PVDF solid particles was 14%, and the mass fraction of polyvinylpyrrolidone was 5%. The mixed solvent system was continuously stirred at a speed of 8000 rpm at room temperature for 4h, and after standing for 12h to remove bubbles, a spinning solution without bubbles and phase separation was obtained, which was used for electrospinning.
[0065] (3) Preparation of composite nanofiber using electrospinning technology:
[0066] The electrospinning machine is used to spin the spinning solution. The drum receiving device is used to prepare the composite nanofiber with uniform thickness. The spinneret fixed on the receiving device can move linearly and uniformly left and right. First, the spinning solution is transferred to the push pump. The push pump is adjusted to fill the plastic tube with the spinning solution. Finally, the high-voltage power supply is connected. The positive electrode of the power supply is connected to the needle. The receiving device and the push pump are connected to the ground. A layer of tin box paper is covered on the drum receiving device to carry the nanofiber. Adjust the working parameters. The receiving distance is 20 cm. The power supply voltage is 6 KV. The flow rate of the push pump is adjusted to 1 mL / h. The air conditioner and dehumidifier are used to control the environmental temperature to 35℃ and the relative humidity to 50%. After 72 hours, the nanofiber is prepared. The tin paper is placed in the oven at 35℃ for drying. Finally, the polyvinylidene fluoride composite nanofiber is obtained.
[0067] (4) The composite nanofiber aerogel is prepared by freeze-drying technology:
[0068] The mixed solvent is prepared by mixing tert-butyl alcohol and ultrapure water in a volume ratio of 4:1 (v / v). The cyanidin extract obtained in step (1) and the polyvinylidene fluoride nanofiber obtained in step (3) are added. Then, water-based polyurethane (solid content 35%) is added. The stable dispersion liquid is formed by high-speed homogenization at 8000 rpm for 3 min, which is the polyvinylidene fluoride short fiber dispersion liquid. The amount of cyanidin extract is 6wt% of the mass of polyvinylidene fluoride short fiber dispersion liquid. The amount of polyvinylidene fluoride composite nanofiber is 2wt% of the mass of polyvinylidene fluoride short fiber dispersion liquid. The amount of water-based polyurethane is 4wt% of the mass of polyvinylidene fluoride short fiber dispersion liquid.
[0069] The ice crystal template is constructed by transferring to the 48-hole mold and directional freezing at -20℃ for 24h. Finally, the hierarchical porous nanofiber composite aerogel freshness indicator label is obtained by freeze-drying at -50℃ / 10Pa for 24h.
[0070] The composite nanofiber aerogel indicator label prepared in Example 3 is applied to shrimp as the research object: fresh shrimp samples are selected and placed in a preservation box and stored at 25℃. The aerogel indicator label is fixed on the inner top wall of the packaging box using food-grade double-sided tape with a distance of 3cm from the sample. The TVB-N detection is based on GB 5009.228-2016. If Figure 4As shown, the shrimp initial TVB-N value is 4.27 mg / 100 g, at this time the shrimp is fresh state, the color of the nanofiber composite aerogel presents purple; the nanofiber composite aerogel color presents light purple at the 18th hour of storage, the TVB-N value is 16.38 mg / 100 g, at this time the shrimp is sub-fresh state; after 24 h of storage, the TVB-N value of the shrimp becomes 20.37 mg / 100 g, at this time the shrimp enters the state of corruption, the nanofiber composite aerogel changes from light purple to blue, after 30 h of storage, with the increase of the corruption degree of the shrimp, the nanofiber composite aerogel presents dark blue. This shows that the prepared nanofiber composite aerogel can quickly respond to the change of the corruption gas in the environment and can clearly indicate the freshness state of the shrimp.
[0071] It should be noted that the above-mentioned embodiments are only used to illustrate but not to limit the technical solutions described in the present application; therefore, although the present application has been described in detail with reference to the above-mentioned embodiments, those skilled in the art should understand that the present application can still be modified or replaced equivalently; and all technical solutions and improvements without departing from the spirit and scope of the present application should be covered in the scope of claims of the present application.
Claims
1. A method for preparing a nanofiber composite aerogel freshness indicator label, characterized in that, Includes the following steps: Step 1: Anthocyanin extraction: The raw material containing anthocyanins is washed and dried. The dried raw material is crushed and collected by sieving. The powder is added to ethanol to form a mixed solution. The resulting mixture is stirred and extracted in the dark. After stirring and extraction, it is filtered to obtain the extract. The ethanol is then evaporated and dried to remove the ethanol. The remaining residual solution is the anthocyanin extract. Step 2: Preparation of spinning solution: PVDF and polyvinylpyrrolidone were dissolved together in a dual solvent system of N,N dimethylformamide and acetone. The solution was stirred and dissolved at room temperature, and then allowed to stand to defoam before spinning. Step 3: Prepare nanofibers using electrospinning technology: The spinning solution prepared in step two was spun using electrospinning technology. First, the spinning solution prepared in step two was injected into a syringe. Then, the spinning parameters were set and the spinning was carried out. Tin foil was used as the receiving substrate and collected by a rotating drum. Finally, polyvinylidene fluoride composite nanofibers were obtained. Step 4: Prepare nanofiber indicator aerogel using freeze-drying technology: The polyvinylidene fluoride composite nanofibers obtained in step 3 and the anthocyanin extract obtained in step 1 were added to a mixed solution of tert-butanol and ultrapure water, and then waterborne polyurethane was added as a binder. After homogenization, a polyvinylidene fluoride short fiber dispersion was obtained. The polyvinylidene fluoride short fiber dispersion was then pre-frozen and then freeze-dried to obtain a nanofiber composite aerogel freshness indicator label.
2. The method for preparing a nanofiber composite aerogel freshness indicator label according to claim 1, characterized in that, The anthocyanin-containing raw materials mentioned in step one include black goji berries, purple cabbage, and butterfly pea flower anthocyanins; the drying temperature is 30-50℃, and the drying time is 24-48h; the mesh size of the sieve is 40-50 mesh; the ratio of the powder to ethanol is 1kg:10L.
3. The method for preparing a nanofiber composite aerogel freshness indicator label according to claim 1, characterized in that, The stirring and extraction time in step one is 8-12 hours, and the evaporation and drying temperature is 45-50℃, with an evaporation time of 2-2.5 hours.
4. The method for preparing a nanofiber composite aerogel freshness indicator label according to claim 1, characterized in that, In step two, the PVDF mass fraction in the spinning solution is 10-16%; the polyvinylpyrrolidone mass fraction in the spinning solution is 5%; the volume ratio of the N,N dimethylformamide and acetone solutions is 4-2:1; the stirring time at room temperature is 2-4 hours; and the standing defoaming time is 10-12 hours.
5. The method for preparing a nanofiber composite aerogel freshness indicator label according to claim 1, characterized in that, The spinning parameters set in step three are as follows: the voltage applied by the high-voltage power supply is 6KV, the receiving distance is 15-20cm, the solution propulsion rate is 1mL / h, the spinning temperature is 30-35℃, and the relative humidity is 40%-50%.
6. The method for preparing a nanofiber composite aerogel freshness indicator label according to claim 1, characterized in that, In step four, the volume ratio of tert-butanol to ultrapure water is 4:1; the amount of polyvinylidene fluoride composite nanofibers is 0.5-3 wt% of the mass of the polyvinylidene fluoride short fiber dispersion; the amount of anthocyanin extract is 3-7 wt% of the mass of the polyvinylidene fluoride short fiber dispersion; the amount of waterborne polyurethane is 3-5 wt% of the mass of the polyvinylidene fluoride short fiber dispersion; and the homogenization conditions are: rotation speed of 8000 rpm and time of 3 min.
7. The method for preparing a nanofiber composite aerogel freshness indicator label according to claim 1, characterized in that, The pre-freezing conditions described in step four are: -20℃, 20-24h; the freeze-drying conditions are: -50℃, 10Pa, 24-36h.
8. The nanofiber composite aerogel freshness indicator label prepared according to any one of claims 1-7, characterized in that, The nanofiber composite aerogel freshness indicator label has an interconnected macroporous structure, combining low density and high porosity.
9. The nanofiber composite aerogel freshness indicator label according to claim 8 is used for detecting the freshness of meat.
10. The nanofiber composite aerogel freshness indicator label according to claim 9 is used to detect the freshness of meat, and the specific steps are as follows: the nanofiber aerogel is cut into an appropriate size and placed inside the meat packaging container, while maintaining physical isolation from the meat; as the storage time is extended, the volatile gases characteristic of meat spoilage are continuously released, and these gases enter the porous structure of the indicator label through diffusion, reacting with the anthocyanin substances loaded on the aerogel, causing a color change in the label; when the meat changes from fresh to not fresh, the color of the corresponding indicator film changes, thereby indicating the freshness status of the meat; thus, the freshness of the meat can be judged in a timely manner based on the color change, achieving visual detection.